The Effect of Audit Opinion, Solvency and Profitability on Audit Delay in Companies Listed on the Indonesia Stock Exchange - Nurhasanah Nurhasanah; Husaini Husaini; Yesi Meldawati (Management Research and Behavior Journal, 2022)
This study aims to examine the effect of audit opinion, solvability and profitability on audit delay in companies listed on the Indonesia Stock Exchange. The sample in this study were all companies listed on the Indonesia Stock Exchange. In sampling, the author uses a purposive sampling technique, namely the sampling method using certain criteria. Data obtained from the publication of the Indonesia Stock Exchange. This study uses as many as 53 sample with multiple linear regression estimates. The results of the study found that the profitability variable had a negative and significant effect on audit delay, while audit opinion and solvability had not effected on the audit delay variable.